A class-E amplifier for a loosely coupled inductive power transfer system with multiple receivers - Sutor, Alexander; Heining, Martin; Buchholz, Rainer (Energies, 2019)
We present a method for optimizing the electronic power system for a new type of photobioreactor or photoreactor in general. In the case of photobioreactors, photosynthetic active microorganisms or cells are grown. A novel concept for the illumination of photobioreactors was necessary, as the external illumination of those reactors leads to a limited penetration depth of light. Due to the limited penetration depth, no standard reactors can be use for cultivation, but custom made reactors with very small volume to surface ratio have to be used. This still prevents the technology from a large scale industrial impact. The solution we propose in this paper is an internal illumination via Wireless Light Emitters. This increases the manageable culture volume of photosynthetic active microorganisms or cells. The illumination system is based on floating light emitters, which are powered wirelessly by near field resonant inductive coupling. The floating light emitters are able to illuminate a photobioreactor more homogeneously than external illumination systems do. We designed a class-E amplifier and field coils to produce an intermediate frequency electromagnetic field inside the reactor. An appropriate magnetic flux density was found to be approx. B = 1mT and the driving frequency is f = 176 kHz. We conducted experiments with a laboratory size photoreactor. The cultivation volume was 30 L containing up to 3000 WLEs. The maximum electric power input was more than 300W and we calculated an efficiency of up to 76%.
CRIS-Team Scopus Importer:2019-05-07
Keywords: Class-E amplifier; Photobioreactor; Wireless light emitter; Wireless power transfer

A Method for Optimizing the Field Coils of Internally Illuminated Photobioreactors - Sutor, Alexander; Heining, Martin; Lindenberger, Christoph; Buchholz, Rainer (Proceedings of INTERMAG2014, 2014)

A new approach to quantify system efficiency with dissolved oxygen isotopes during engineered growth of Galdieria sulphuraria - Mader, Michael; Schwerna, Philipp; Buchholz, Rainer; van Geldern, Robert; Barth, Johannes (Algal Research, 2017)
The microalgae Galdieria sulphuraria was grown in a first technical approach in a closed system experiment for 29 days. In this time period, 6 separate flasks were sampled for oxygen concentration and their stable isotope ratios (O-18/O-16) in dissolved and headspace phases. The oxygen isotope composition of the water was also analysed as an input for the transfer of its O-18/O-16 ratio to molecular oxygen via production by algae. This photosynthetic transfer of the isotope composition of water was counterbalanced by oxygen consumption that enriched both phases in O-18. For this reason, neither dissolved oxygen nor oxygen in the headspace reached the O-18-depleted oxygen isotope ratio of H2O despite excessive photosynthesis. Oxygen that was produced by photosynthesis accumulated with a yield of 13.96 mmol L-1 in the headspace and with 0.5 mmol L-1 in the fluid phase. This difference was due to rapid degassing of the solution. It was further amplified by preferential consumption of the dissolved O-2 phase. In order to quantify oxygen production and its consumption we determined photosynthesis/respiration (P/R) ratios with a formula that combined O-2 concentrations and its isotope ratios. It revealed a P/R ratio of 7.7 after 11 days. After this it decreased again and moved towards dominance of respiration. With this work our results introduce a new method to monitor the growth and efficiency of algae in controlled experiments.
Keywords: Dissolved oxygen; Stable isotopes; Algae growth; Closed system; Respiration; Galdieria sulphuraria

An optimized method and a dominant selectable marker for genetic engineering of an industrially promising microalga-Pavlova lutheri - Prasad, Binod; Lein, Wolfgang; Lindenberger, Christoph; Buchholz, Rainer; Vadakedath, Nithya (Journal of Applied Phycology, 2019)
The marine microalga Pavlova lutheri has great nutritional value as it synthesizes and accumulates higher amounts of polyunsaturated fatty acids (PUFAs). It is commonly used in aquaculture. However, no transformation procedure has been realized for this industrially important microalga so far. Here, we report an efficient protocol for the nuclear transformation of P. lutheri. Agrobacterium-mediated transformation (AMT) of P. lutheri with a mutated genomic clone of phytoene desaturase (pds) gene, pds-L504R, from Haematococcus pluvialis yielded norflurazon-resistant P. lutheri cells. Ideal co-cultivation conditions for achieving higher numbers of transformants was found to be artificial seawater (ASW) medium, 100 mu M acetosyringone, and a 24-h co-cultivation at 25 +/- 1 degrees C. The integration of the introduced gene into the nuclear genome of P. lutheri was shown by PCR amplification of the T-DNA sequences from the genomic DNA of transformants and Southern blot analysis using T-DNA sequences as probes. The transgene expressed efficiently as evidenced by the results of stability and tolerance study, and the qRT-PCR analysis. Results clearly demonstrate the application of AMT approach and pds gene as a dominant selectable marker for the genetic engineering of P. lutheri for fundamental studies and biotechnological applications.
CRIS-Team WoS Importer:2019-04-25

A novel model for studying baculovirus infection process - Lindenberger, Christoph; Pflug, Lukas; Hübner, Holger; Buchholz, Rainer (Biotechnology and Bioprocess Engineering, 2012)
In this paper, a new Ansatz for modelling the Baculovirus infection cycle is presented. The base of this model is the cell cycle distribution at the time of infection. It is possible to calculate the growth of the culture and the initiation of virus processing by considering cell cycle distribution. By taking into account the length of the viral genome and the polymerase activity, it is possible to calculate the virus production rate, which underlies a logistic growth. In the present work, a new hypothesis explaining the accelerated death rates of infected cells has been introduced. This assumption provides the possibilities of performing calculation without any fixed time intervals. The simulation was tested by comparing experimental data with the model prediction. Therefore, cell cycle distributions over the culture time and the growth behaviour of infected and non-infected insect cells were measured. A model, Baculovirus coding for GFP was employed for the present investigation, as it allows tracking the infection and determining the effectiveness of the infection, which is highly dependent on the cell density at the time of infection (TOI). Furthermore, the new model is is taken to simulate data gained from literature about virus release and adsorption. The new assumptions make the model more independent to fit into different cultivation systems.
Keywords: baculovirus; modelling; insect cells; infection cycle

Application of light-emitting diodes (LEDs) in cultivation of phototrophic microalgae: current state and perspectives - Becker, Anna; Glemser, M.; Heining, Martin; Schmidt, J.; Becker, A.; Garbe, Daniel; Buchholz, Rainer; Brueck, T. (Applied Microbiology and Biotechnology, 2016)
The quality and regulation of the incident light is crucial in microalgae cultivation processes. Depending on wavelength, spectrum, and intensity, growth characteristics and biochemical composition of these organisms vary. With mainly fluorescent lamps (FL) used previously for illumination, such variabilities could not be studied adequately due to their broad emission spectrum. In contrast, light-emitting diodes (LEDs) emit a very narrow wavelength band and enable flexible photobioreactor designs due to their small size. This review provides a condensed overview on the application of LEDs in microalgal cultivation processes. It summarizes the current availability and applicability of LED technologies as an illumination source for research-focused photobioreactor systems. A particular focus is the use of narrow-wavelength LEDs to address fundamental as well as applied aspects of light color on algae biomass and value-added compound formation. In this respect, the application of internal and external illumination systems is reviewed together with trends in the industrial use of LED systems to intensify algae process efficiency.
Keywords: LED; Light-emitting diodes; Microalgae; Photobioreactor; Wavelengths

Assessing viability of extracorporeal preserved muscle transplants using external field stimulation: a novel tool to improve methods prolonging bridge-to-transplantation time. - Taeger, Christian; Friedrich, Oliver; Dragu, Adrian; Weigand, Annika; Hobe, Frieder; Drechsler, Caroline; Geppert, Carol-Immanuel; Arkudas, Andreas; Münch, Frank; Buchholz, Rainer; Pollmann, Charlotte; Schramm, Axel; et al. (Scientific Reports, 2015)
Preventing ischemia-related cell damage is a priority when preserving tissue for transplantation. Perfusion protocols have been established for a variety of applications and proven to be superior to procedures used in clinical routine. Extracorporeal perfusion of muscle tissue though cumbersome is highly desirable since it is highly susceptible to ischemia-related damage. To show the efficacy of different perfusion protocols external field stimulation can be used to immediately visualize improvement or deterioration of the tissue during active and running perfusion protocols. This method has been used to show the superiority of extracorporeal perfusion using porcine rectus abdominis muscles perfused with heparinized saline solution. Perfused muscles showed statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. The combination of extracorporeal perfusion and external field stimulation may improve organ conservation research.

Biosorption of Neodymium by Selected Photoautotrophic and Heterotrophic Species - Heilmann, Marcus; Jurkowski, Wojciech; Buchholz, Rainer; Brueck, Thomas; Becker, Anna (Journal of Chemical Engineering & Process Technology, 2015)
In a search for alternative methods for isolation of rare earth elements from diluted solutions, a possibility of their preconcentration on biomass of mainly phototrophic species, that can be easily cultivated in open or closed systems, was investigated in this study. A screening of 19 biological species, consisting of 17 microalgae, one yeast and one moss, in regard to the biosorption of neodymium (Nd) on their lyophilized biomass was performed. Maximum sorption capacity (qm) was determined after incubation for 3 h at room temperature and centrifugation through measuring the Nd content in the supernatant via a spectrophotometric assay. The obtained qm values ranged from 0.26 mmol*g-1 for Chlamydomonas reinhardtii to 0.48 mmol*g-1 for Calothrix brevissima and up to 0.74 mmol*g-1 for Physcomitrella patens. Kinetic measurements show the reaching of qm after 30 min for C. reinhardtii and 180 min for P. patens. Based on titration studies the proton exchange capacity was found to be 0.39 mmol*g-1 for C. reinhardtii and 0.44 mmol*g-1 for P. patens leading to a conclusion that proton exchange was mainly responsible for the biosorption mechanism. To our knowledge it is the first report of screening regarding such a wide scope of microalgae for a sorption of Nd. <
UnivIS-Import:2018-09-05:Pub.2015.tech.ITC.cbiove.biosor
Keywords: biosorption; microalgae; lyophilized biomass; recovery of Nd from highly diluted solutions; mechanism

Biosorption of Neodymium by Selected Photoautotropic and Heterotropic Species - Heilmann, Marcus; Jurkowski, Wojciech; Buchholz, Rainer; Brueck, Thomas; Becker, Anna (Journal of Chemical Engineering & Process Technology, 2015)
In a search for alternative methods for isolation of rare earth elements from diluted solutions, a possibility of their preconcentration on biomass of mainly phototrophic species, that can be easily cultivated in open or closed systems, was investigated in this study. A screening of 19 biological species, consisting of 17 microalgae, one yeast and one moss, in regard to the biosorption of neodymium (Nd) on their lyophilized biomass was performed. Maximum sorption capacity (qM) was determined after incubation for 3 h at room temperature and centrifugation through measuring the Nd content in the supernatant via a spectrophotometric assay. The obtained qM values ranged from 0.26 mmol*g-1 for Chlamydomonas reinhardtii to 0.48 mmol*g-1 for Calothrix brevissima and up to 0.74 mmol*g-1 for Physcomitrella patens. Kinetic measurements show the reaching of qM after 30 min for C. reinhardtii and 180 min for P. patens. Based on titration studies the proton exchange capacity was found to be 0.39 mmol*g-1 for C. reinhardtii and 0.44 mmol*g-1 for P. patens leading to a conclusion that proton exchange was mainly responsible for the biosorption mechanism. To our knowledge it is the first report of screening regarding such a wide scope of microalgae for a sorption of Nd.
Keywords: Biosorption; Microalgae; Lyophilized biomass; Recovery of Nd from highly diluted solutions; Mechanism

Cell Disruption and Pressurized Liquid Extraction of Carotenoids from Microalgae - Taucher, Josephine; Baer, Sascha; Schwerna, Philipp; Hofmann, Dominik; Hümmer, Magdalena; Buchholz, Rainer; Becker, Anna (Journal of Thermodynamics & Catalysis, 2016)
Microalgae are very promising organisms for the production of high-value compounds such as carotenoids. Nevertheless, their commercial use is so far hampered by the lack of efficient processes and currently feasible for very few strains. One of the most relevant factors is the high effort for downstream processing, e.g., cell disruption and extraction. Thus, the presented studies were dedicated to investigate and optimize these two steps for carotenoid production with microalgae. Six different cell disruption techniques (high pressure homogenizer, ball mill, Ultra Turrax, repeated freeze and thaw, freeze-drying, ultra-sonication) were compared in lab scale for three species: Haemotococcus pluvialis, Chromochloris zofingiensis and Chlorella sorokiniana. The carotenoid recovery was determined via HPLC-UV/Vis after pressurized solvent extraction. Furthermore, factors influencing the applied extraction methods such as solvent, temperature, duration and number of cycles were optimized in order to reach highest recovery rates. While rough mechanical methods such as ball mill and high pressure homogenizer showed the highest effectivity for cell disruption of all three investigated strains, the influence of non-mechanical methods - i.e., repeated freeze and thaw cycles - on the efficiency of the extraction of astaxanthin, lutein and β-carotene increased reversely proportional to cell size and cell wall rigidity. For H. pluvialis repeated freezing and thawing resulted in a factor 240 times lower extraction yield compared to high pressure homogenizer, while both methods were comparable for C. sorokiniana. From six tested solvents, dichloromethane resulted in the highest carotene recovery yield, three times higher in comparison to n-hexane. Variation of the extraction temperature from room temperature to 120°C showed an optimum at 60°C. Nearly complete extraction was reached after one cycle of 10 minutes. The data presented here demonstrate the necessity of lab scale optimization of cell disruption and extraction process for future upscaling.
Keywords: H. pluvialis; C. sorokiniana; C. zofingiensis; Carotenoids; Cell disruption; Pressurized liquid extraction; HPLC

Correction to: A new approach for calculating microalgae culture growth based on an inhibitory effect of the surrounding biomass (Bioprocess and Biosystems Engineering, (2021), 10.1007/s00449-021-02550-6) - Jung, Sun Hwa; McHardy, Christopher; Rauh, Cornelia; Jahn, Alexander; Luzi, Giovanni; Delgado, Antonio; Buchholz, Rainer; Lindenberger, Christoph (Bioprocess and Biosystems Engineering, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00449-021-02594-8.
CRIS-Team Scopus Importer:2021-06-25

Cultivation of phototrophic microorganisms in photobioreactors illuminated via Wireless Light Emitter - Heining, Martin; Sutor, Alexander; Lindenberger, Christoph; Stute, Stephanie; Buchholz, Rainer (10th European Symposium on Biochemical Engineering Sciences and 6th International Forum on Industrial Bioprocesses, 2014)

Decellularized xenogenic meniscus as a replacement for meniscal tissue - Körber, Ludwig; Mauer, Julia; Rösch, Rebecca; Tluczynski, Katharina; Schwarz, Silke; Rotter, Nicole; Buchholz, Rainer; Breiter, Roman (European Cells and Materials, Vol. 31, Suppl. 1, 2016)

Die Kraft aus der Pflanze - Becker, Anna; Buchholz, Rainer; Brueck, Thomas (2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.ITC.cbiove.diekra

Examination of Infection parameters for Replication of Israeli Isolate of Koi Herpesvirus in Common Carp Brain Cells - Jordan, Lisa; Amtmann, Anette; Heidenreich, Elke; Christian, Juergen; Buchholz, Rainer; Becker, Anna (Journal of Virology and Antiviral Research, 2017)
Research on koi herpesvirus (KHV) is mainly focused on fish trials for the investigation of virus entry, disease progress and immunological responses within the organism in order to develop new diagnostic and treatment strategies. However, examination of in vitro-replication of KHV might give useful insights supporting the understanding of this pathogen as well as contributing to the development of new methods for diagnostic purposes and/or vaccine development. Nevertheless, until today, only few studies have been published on this matter. Thus, this work concerns investigation of in vitro-replication of the Israeli isolate of KHV, KHV-I, in the widely used common carp brain cells (CCB) to identify the parameters leading to high-quality virus stock with high titers for further applications. Therefore, the propagation of the KHV-I at the influence of various cell densities at inoculation, virus load and time of harvest on the propagation of KHV-I was examined. Obtained results indicate that inoculation with relatively high cell densities is advantageous since the highest titers could be reached for 60 000 and 75 000 cells/cm2 already 3 days after inoculation. In contrast, the use of too high virus load for inoculation with too low cell density can result in much lower maximum or even decrease in virus titers. While viral DNA showed to be relatively stable after reaching the maximum, the infectivity of the virus can decrease shortly after the peak. Therefore, selection of the right combination of infection parameters is crucial for reaching the appointed goal. This work gives valuable insights into the replication of KHV-I in CCB cells and indicates the differences between various KHV isolates regarding in vitro-propagation.
Keywords: Common carp brain cells; Koi herpesvirus; Multiplicity of infection; Time of infection; Time of harvest; Replication; Virus titer

Extracorporeal perfusion - reduced to a one-way infusion. - Taeger, Christian Dirk; Friedrich, Oliver; Horch, Raymund E.; Drechsler, Caroline; Weigand, Annika; Hopf, Fabio; Geppert, Carol-Immanuel; Münch, Frank; Birkholz, Torsten; Wenzel, Carina; Geis, Sebastian; Prantl, Lukas; et al. (Clinical hemorheology and microcirculation, 2017)
BACKGROUND Extracorporeal perfusion (EP) is moving into focus of research in reconstructive and transplantation medicine for the preservation of amputates and free tissue transplants. The idea behind EP is the reduction of ischemia-related cell damage between separation from blood circulation and reanastomosis of the transplant. Most experimental approaches are based on a complex system that moves the perfusate in a circular course. OBJECTIVE AND METHODS In this study, we aimed to evaluate if a simple perfusion by an infusion bag filled with an electrolyte solution can provide acceptable results in terms of flow stability, oxygen supply and viability conservation for EP of a muscle transplant. The results are compared to muscles perfused with a pump system as well as muscles stored under ischemic conditions with a one-time intravasal flushing with Jonosteril. RESULTS With this simple method a sufficient oxygen supply could be achieved and functionality could be maintained between 3.35 times and 4.60 times longer compared to the control group. Annexin V positive nuclei, indicating apoptosis, increased by 9.7% in the perfused group compared to 24.4% in the control group. CONCLUSIONS Overall, by decreasing the complexity of the system, EP by one-way infusion can become more feasible in clinical situation

Hydroxyethyl starch solution for extracorporeal tissue perfusion - Taeger, Christian; Friedrich, Oliver; Drechsler, Caroline; Weigand, Annika; Hobe, Frieder; Geppert, Carol-Immanuel; Münch, Frank; Birkholz, Torsten; Buchholz, Rainer; Horch, Raymund E.; Präbst, Konstantin; Buchholz, Rainer (Clinical hemorheology and microcirculation, 2016)
In the field of free flap transfer in reconstructive surgery, the trans- or replanted tissue always undergoes cell damage during ischemia to a more or less strong extent. In previous studies we already showed that conserving muscle transplants by means of extracorporeal perfusion over a period of 6 hours by using a crystalloid solution for perfusion. However, we observed significant edema formation. In this study we aimed at reducing the edema formation by using an iso-oncotic colloid as perfusion solution. This way we want to evaluate a possible new application of hydroxyl-ethyl starch in an extracorporeal setup to exploit potential benefits of the colloid.Examined parameters include the muscles' functionality with external field stimulation, histological examination and edema formation. Perfused muscles showed a statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. Substituting the electrolyte perfusion solution with a colloidal one shows the tendency to reduce the edema formation but without statistical significance.

Improving Joint Learning of Suspended and Adherent Cell Detection Using Low-Pass Monogenic Phase and Transport of Intensity Equation - Mualla, Firas; Schöll, Simon; Sommerfeldt, Björn; Steidl, Stefan; Buchholz, Rainer; Hornegger, Joachim (IEEE 11th International Symposium on Biomedical Imaging (ISBI), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.improv_8

Influence of the phase effect on gradient-based and statistics-based focus measures in bright field microscopy - Schöll, Simon; Mualla, Firas; Sommerfeldt, Björn; Steidl, Stefan; Maier, Andreas; Buchholz, Rainer; Hornegger, Joachim (Journal of Microscopy, 2014)
Autofocusing is essential to high throughput microscopy and live cell imaging and requires reliable focus measures. Phase objects such as separated single Chinese hamster ovary cells are almost invisible at the optical focus position in bright field microscopy images. Because of the phase effect, defocused images of phase objects have more contrast. In this paper, we show that widely used focus measures exhibit an untypical behaviour for such images. In the case of homogeneous cells, that is, when most cells tend to lie in the same focal plane, both gradient-based and statistics-based focus measures tend to have a local minimum instead of a global maximum at the optical focus position. On the other hand, if images show inhomogeneous cells, gradient-based focus measures tend to yield typical focus curves, whereas statistics-based focus measures deliver curves similar to the case of homogeneous cells. These results were interpreted using the equation describing the phase effect and patch-wise analysis of the focus curves. Bioprocess engineering experts are also influenced by the phase effect. Forty-four focus positions selected by them led to the conclusion that they prefer to look at defocused images instead of those at the optical focus. © 2014 The Authors Journal of Microscopy © 2014 Royal Microscopical Society.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.influe
Keywords: Bright field microscopy; Focus measures; Nontypical focus curves; Phase effect

Inoculation of cyprinid herpesvirus 3 (CyHV-3) on common carp brain cells-influence of process parameters on virus yield - Mletzko, Adam; Amtmann, Anette; Bergmann, Sven M.; Lee, Peiyu Alison; Christian, Juergen; Buchholz, Rainer; Becker, Anna (In Vitro Cellular & Developmental Biology - Animal, 2017)
Research of cyprinid herpesvirus 3 (CyHV-3) is focused on the infection mechanism and disease development in animals using genetic and immunological approaches to improve treatments and diagnostics. In contrast, only few tried to investigate the CyHV-3 replication behaviour in available cell cultures. Whereas, obtaining high virus yields by in vitro replication enables achieving of the mentioned above goals easier and more reliable. The following work presents an attempt to illuminate the KHV replication in common carp brain (CCB) cell cultures from the engineering point of view. The isolate KHV-TP30 was used testing the influence on process parameters, such as multiplicity of infection (MOI), time of infection (TOI) and time of harvest (TOH). Virus concentrations and infectivity at different time points of infection were examined using hydrolyzed probe qPCR (Gilad et al. 2004) and 50% tissue culture infectivity dose (TCID50). The data obtained show that while the amount of the virus DNA remains constant after reaching its maximum, the infectivity of the virus decreases. Thus, especially, TOH can be crucial for generating a high-quality virus stock. Applying optimized parameters improved the infectivity of the harvested virus and reached a robust titre as high as 1.9 × 108 TCID50/mL. To our knowledge, so far, there is no information in the peer-reviewed literature showing comparably high virus titres. Such virus yields not only facilitate conduction of further studies, including stability tests of the virus stock under various supplementation or disinfection trails, but also provide enough virus material to perform more detailed examinations of the infection mechanism.
Keywords: Common carp brain; CyHV-3; Multiplicity of infection; Tissue culture infective dose 50%

Internal Illumination of photobioreactors via Wireless Light Emitter – a proof of concept - Heining, Martin; Sutor, Alexander; Lindenberger, Christoph; Stute, Stephanie; Buchholz, Rainer (Young Algaeneers Symposium, 2014)

Internal illumination of photobioreactors via wireless light emitters: a proof of concept - Heining, Martin; Sutor, Alexander; Stute, Stephanie; Lindenberger, Christoph; Buchholz, Rainer; Buchholz, Rainer (Journal of Applied Phycology, 2015)
A novel concept for internal illumination of photobioreactors via wireless light emitters (WLEs) has been developed to increase the manageable culture volume of photosynthetic active microorganisms or cells. The illumination system is based on free suspendable light emitters, which are powered wirelessly by near-field resonant inductive coupling and, therefore, are able to illuminate a photobioreactor more homogeneously than external illumination systems. Since an intermediate frequency electromagnetic field (IF-EMF) acts inside the reactor, the impact of an IF-EMF (B = 0.95 mT, f = 178 kHz) on the green alga Chlamydomonas reinhardtii is determined. The growth rate, the achieved cell dry weight, and the maximum photosynthetic yield Y (0) are unaffected by the applied IF-EMF. Furthermore, a negative effect of the potentially occurring mechanical stress due to the suspended WLE can be excluded. A culture which is mechanically stressed by 125 WLEs per liter shows the same maximal growth rate of 2.29 day(-1) as a control culture. Finally, the comparison of an externally illuminated photobioreactor and a via WLE internally illuminated photobioreactor shows the same growth rates in the exponential growth phase. However, the growth rate in the linear phase is more than twice the rate of the externally illuminated control culture, resulting in a more than 80 % higher achieved biomass. Light profiles over the cross section of both reactor types show clearly that the internal illumination via WLE results in a more uniform light distribution and a higher average light intensity in the reactor.
Keywords: Photobioreactor; Internal illumination; Wireless light emitter; Magnetic field; Wireless energy transfer; Near-field resonant inductive coupling

Licht ins Grüne - Glemser, Matthias; Schmidt, Johannes; Heining, Martin; Becker, Anna; Arnold, Oliver; Garbe, Daniel; Buchholz, Rainer; Brueck, Thomas (2015)
UnivIS-Import:2017-12-18:Pub.2015.tech.ITC.cbiove.lichti

Measuring average rheological quantities of cell monolayers in the linear viscoelastic regime - Dakhil, Haider; Gilbert, Daniel; Malhotra, Deepika; Limmer, Anja; Engelhardt, Hannes; Amtmann, Anette; Hansmann, Jan; Hübner, Holger; Buchholz, Rainer; Friedrich, Oliver; Wierschem, Andreas (Rheologica Acta, 2016)
During the last decades, the rheology of cells has been studied almost entirely in single cells. While cell-to-cell variation is typically very large and most studies were carried out in the nonlinear viscoelastic regime, we quantify average linear viscoelastic cell properties like storage and loss moduli and normal stress in monolayers of different cell types showing that murine 3T6 fibroblasts, human fibroblasts, and HeLa cells differ considerably in their storage modulus. To this end, we modified a commercial rheometer to set up a parallel-disk configuration at gap widths of a few micrometers and optically detected the cell concentration in the gap. This enables studying the linear viscoelastic behavior of the cells and permits quantifying the impact of drugs affecting the cytoskeleton or the extracellular matrix connection. Thus, due to its high-content approach, without the need of treating the samples in the rheometer, this envisions the use of this method as a fast diagnostic tool. The method also allows for quantitatively studying of the impact of pre-stress on the storage and loss moduli of the cells.
Keywords: Cell rheology; Linear viscoelasticity; Narrow-gap rheometry; Parallel-disk configuration; Cell monolayer; Biochemical treatment; Pre-stress; Primary cells; Cell lines

Method for Optimizing the Field Coils of Internally Illuminated Photobioreactors - Sutor, Alexander; Heining, Martin; Lindenberger, Christoph; Buchholz, Rainer (IEEE Transactions on Magnetics, 2014)
We present a method for optimizing the design of field coils for a new type of photobioreactor (PBR). In those PBRs, photosynthetic active microorganisms or cells are grown. A novel concept for the illumination of PBRs was necessary, as the external illumination of those reactors leads to a limited penetration depth of light. The solution we propose is an internal illumination via wireless light emitters (WLEs). This increases the manageable culture volume of photosynthetic active microorganisms or cells. The illumination system is based on floating light emitters, which are powered wirelessly by near field resonant inductive coupling. The floating light emitters are able to illuminate a PBR more homogeneously than external illumination systems. We designed field coils to produce an intermediate frequency electromagnetic field inside the reactor. We chose a magnetic flux density B = 0.95 mT and a frequency f = 178 kHz. To reach optimal efficiency, the magnetic field has to be as homogeneous as possible. We demonstrate how this optimization can be performed with the method of differential evolution. Using the optimized field coil design, the minimum magnetic field was increased by almost 10% keeping the number of ampere-turns constant. A comparison of the light profiles over the cross section of both reactor types show clearly that the internal illumination via WLE results in a more uniform light distribution and a higher average light intensity in the reactor. An impact of the magnetic field on the green alga Chlamydomonas reinhardtii could be excluded by comparing the growth rate, the achieved cell dry weight and the maximum photosynthetic yield with and without applied magnetic field. Furthermore, a negative effect of the potentially occurring mechanical stress due to the suspended WLE can be excluded. A culture which is mechanically stressed by 125 WLE per liter shows the same maximal growth rate as a control culture. Finally, the comparison of an externally and a via WLE internally illuminated PBR shows the same growth rates in the exponential growth phase. However, the growth rate in the linear phase is more than twice the rate of the externally illuminated control culture, resulting in a more than 80% higher achieved biomass.
Keywords: Global optimization; internal illumination; near field resonant inductive coupling; photobioreactor (PBR); wireless energy transfer; wireless light emitter (WLE)

Photobioreactors with internal illumination - A survey and comparison - Buchholz, Rainer; Heining, Martin; Buchholz, Rainer (Biotechnology Journal, 2015)
The idea of internally illuminated photobioreactors has existed since the 1990s and various systems were developed since. Recently, the interest in these systems has been on the rise again, due to the increased production of and research on high-value products and recombinant proteins from microalgae and plant cell cultures. While promising results in lab-scale have been achieved, the potential of photoautotrophic or mixotrophic production of these compounds is limited due to the lack of scalable photobioreactors, which could be overcome by internally illuminated systems. In this article, we review different internally illuminated photobioreactors from the last two decades and classify them into two major groups. The photobioreactors are compared based on the ratio of illuminated surface-to-culture volume and the occupied volume by internal light-emitting elements, and possible obstacles, challenges and future trends are discussed. Looking forward, new technologies and smaller light sources have improved the potential of internally illuminated photobioreactors with internal light sources and will enable these technologies to compete with systems with internal light guides, but only a few of these systems have currently achieved a relevant scale.
UnivIS-Import:2017-07-10:Pub.2015.tech.ITC.cbiove.photob
Keywords: Internal illumination; Light guides; Optical fibers; Photobioreactor; Wireless light emitter

Prolonged Ex vivo expansion and differentiation of naïve murine CD43(-) B splenocytes - Zambrano, Kenny; Jerome, Valerie; Freitag, Ruth; Buchholz, Rainer; Jäck, Hans-Martin; Hübner, Holger; Schuh, Wolfgang; Buchholz, Rainer (Biotechnology Progress, 2016)
Ex vivo expansion of naive primary B cells is still a challenge, yet would open new possibilities for in vitro studies of the immune response or the production of monoclonal antibodies. In our hands, unstimulated murine B cells did not expand in significant numbers, while culture viability decreased rapidly within a few days. Activation mimicking in vivo stimulation through either T cell-independent or T-cell dependent signaling, led to several division cycles, albeit accompanied by irreversible differentiation. By co-culturing B cells under moderate hypothermia (30°C) on live feeder fibroblasts expressing recombinant CD40 ligand (CD154) and by repeatedly transferring cultured B cells to new feeder cell cultures, we could extend the growth of primary mouse B cells compared to cultures maintained at 37°C. B cells under these conditions showed an activated phenotype as shown by the presence of AID and IRF4, two factors required for IgH class switch recombination in antigen-activated B cells. In contrast to cells cultured at 37°C, B cells under hyperthermia did surprisingly not differentiate into Blimp-1 expressing plasmablasts. Thus, the repeated batch process under hyperthermic conditions represents a first step towards the development of a continuous cultivation system for the expansion of primary B cells. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:978-989, 2016.
EVALuna2:13639

Raman Spectrocopy for non-invasive online measuerements of the pH and CO2 concentration in algal cultivations - Koch, Hanna; Noack, Kristina; Stute, Stephanie; Buchholz, Rainer; Will, Stefan (3rd European Congress of Applied Biotechnology (ECAB), 2015)

Revitalisation of a decellularised xenogenic meniscus implant by cells from human synovial membrane - Tluczynski, Katharina; Körber, Ludwig; Schwarz, Silke; Rotter, Nicole; Buchholz, Rainer; Breiter, Roman (European Cells and Materials, Vol. 31, Suppl. 1, 2016)

Stable nuclear transformation of rhodophyte species Porphyridium purpureum: advanced molecular tools and an optimized method - Prasad, Binod; Lein, Wolfgang; Thiyam, General; Lindenberger, Christoph; Buchholz, Rainer; Vadakedath, Nithya (Photosynthesis Research, 2019)
A mutated phytoene desaturase (pds) gene, pds-L504R, conferring resistance to the herbicide norflurazon has been reported as a dominant selectable marker for the genetic engineering of microalgae (Steinbrenner and Sandmann in Appl Environ Microbiol 72:7477–7484, 2006; Prasad et al. in Appl Microbiol Biotechnol 98(20):8629–8639, 2014). However, this mutated genomic clone harbors several introns and the entire expression cassette including its native promoter and terminator has a length > 5.6 kb, making it unsuitable as a standard selection marker. Therefore, we designed a synthetic, short pds gene (syn-pds-int) by removing introns and unwanted internal restriction sites, adding suitable restriction sites for cloning purposes, and introduced the first intron from the Chlamydomonas reinhardtii RbcS2 gene close to the 5′end without changing the amino acid sequence. The syn-pds-int gene (1872 bp) was cloned into pCAMBIA 1380 under the control of a short sequence (615 bp) of the promoter of pds (pCAMBIA 1380-syn-pds-int). This vector and the plasmid pCAMBIA1380-pds-L504R hosting the mutated genomic pds were used for transformation studies. To broaden the existing transformation portfolio, the rhodophyte Porphyridium purpureum was targeted. Agrobacterium-mediated transformation of P. purpureum with both the forms of pds gene, pds-L504R or syn-pds-int, yielded norflurazon-resistant (NR) cells. This is the first report of a successful nuclear transformation of P. purpureum. Transformation efficiency and lethal norflurazon dosage were determined to evaluate the usefulness of syn-pds-int gene and functionality of the short promoter of pds. PCR and Southern blot analysis confirmed transgene integration into the microalga. Both forms of pds gene expressed efficiently as evidenced by the stability, tolerance and the qRT-PCR analysis. The molecular toolkits and transformation method presented here could be used to genetically engineer P. purpureum for fundamental studies as well as for the production of high-value-added compounds.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Agrobacterium tumefaciens; Norflurazon-resistant; Phytoene desaturase; Porphyridium purpureum; Transformation

Terbium Excitation Spectroscopy as a Detection Method for Chromatographic Separation of Lanthanide-Binding Biomolecules - Jurkowski, Wojciech; Heilmann, Marcus; Becker, Anna; Buchholz, Rainer; Brueck, Thomas (ACS Omega, 2020)
Studies of biosorption and bioaccumulation of heavy metals deal mostly with challenging, inhomogeneous, and complex materials. Therefore, most reports describe only application studies, while fundamental research is limited to indirect methods and speculations on the binding mechanisms. In this study, we describe a method for detecting and isolating heavy metal-binding biomolecules directly from crude extracts. The underlying principle is terbium sensitization and fluorescence excitation spectroscopy used offline after a chromatographic run. Compounds interacting with metal ions inevitably change the coordination sphere of terbium, which is reflected in the excitation spectrum leading to metal-specific luminescence. Main advantages of our approach include simple, fast, and inexpensive experiment design, nondestructive measurements, and detection limits far below 1 mg. Here, we have applied our method for three promising biosorbents (green algae, moss, and cyanobacterium) and obtained first information on the character of active compounds isolated from each species.<br

The application of exopolysaccharides (EPS) can prevent viral disease of fish. - Bergmann, Sven Michael; Reichert, Matthias; Hwang, J; Becker, Anna; Lenk, Matthias; Kotterba, Günter; Buchholz, Rainer; Jung, Sunhwa; Gebler, A; Todte, M; Kielpinska, J; Lindenberger, Christoph (Bulletin of the European Association of Fish Pathologists, 2022)
In the frame of investigations on the use of exopolysaccharides (EPS) from Arthrospira platensis in carp and koi cultures, two animal experiments were carried out to assess their efficiency as prophylactic and metaphylactic (therapeutic) measures against koi herpesvirus disease (KHVD). In experiment 1, carp were treated with algae biomass (BM) and EPS before and after infection with European lineage koi herpesvirus (KHV-E). In experiment 2, carp were treated with EPS prior and after the infection with Taiwan isolate of KHV (KHV-T), only prior to infection with higher concentration of EPS or only after the infection with KHV-T. No conclusive protection against KHV was observed in experiment 1 in carp treated with BM. In groups where EPS was applied, carp were protected to a certain extent. In experiment 2, carp were protected significantly against a severe KHVD outbreak. In the prophylactic group, which received a double EPS concentration for six weeks, and in the metaphylactic group, KHVD was stopped. Fish developed antibodies against EPS as well as against KHV at day 30 post infection.<br
Keywords: algae; EPS; KHV; KHVD; inhibition; prophylaxis; metaphylaxis

The application of exopolysaccharides (EPS) can prevent viral disease of fish - Bergmann, S. M.; Reichert, M.; Hwang, J.; Becker, Anna; Lenk, M.; Kotterba, G.; Buchholz, Rainer; Jung, S.; Gebler, A.; Todte, M.; Kielpinska, J.; Lindenberger, Ch. (Bulletin of the European Association of Fish Pathologists, 2022)
In the frame of investigations on the use of exopolysaccharides (EPS) from Arthrospira platensis in carp and koi cultures, two animal experiments were carried out to assess their efficiency as prophylactic and metaphylactic (therapeutic) measures against koi herpesvirus disease (KHVD). In experiment 1, carp were treated with algae biomass (BM) and EPS before and after infection with European lineage koi herpesvirus (KHV-E). In experiment 2, carp were treated with EPS prior and after the infection with Taiwan isolate of KHV (KHV-T), only prior to infection with higher concentration of EPS or only after the infection with KHV-T. No conclusive protection against KHV was observed in experiment 1 in carp treated with BM. In groups where EPS was applied, carp were protected to a certain extent. In experiment 2, carp were protected significantly against a severe KHVD outbreak. In the prophylactic group, which received a double EPS concentration for six weeks, and in the metaphylactic group, KHVD was stopped. Fish developed antibodies against EPS as well as against KHV at day 30 post infection.
CRIS-Team WoS Importer:2023-06-02

The response of newly established cell lines of Spodoptera littoralis to group I and group II baculoviruses - Ahmed, Ibrahim Abdulla; Hübner, Holger; Mamoori, Yaseen Ismael; Buchholz, Rainer (Cytotechnology, 2019)
Autographa californica multiple nucleopolyhedrovirus (AcMNPV) and Spodoptera littoralis multiple nucleopolyhedrovirus (SpliMNPV) belong to group I and group II nucleopolyhedroviruses, respectively and can replicate in a wide range of insect species. In this study, the ability of newly established S. littoralis cell lines to support replication of AcMNPV and SpliMNPV was examined. The microscopic observations showed that the S. littoralis cells infected with AcMNPV exhibited morphological changes such as cells breaking into small bodies and forming apoptosis-like bodies post-infection. Nuclear DNA fragmentation was observed in all AcMNPV-infected cell lines through DNA gel electrophoresis analysis. Therefore, the virus replication was unsuccessful in most of cells, which were able to abort the virus replication. On the other hand, cells that were infected with SpliMNPV did not show similar morphological changes and no small bodies were formed. In addition, SpliMNPV succeeded to infect the cells, replicate, and form viral occlusion bodies inside the infected cells. In suspension culture, S. littoralis cells, which were infected with AcMNPV, accumulated as composed balls in shaker flasks after infection overnight, with cell density decreasing dramatically. In contrast, there was no cell clumping seen in the infected cells with SpliMNPV and the uninfected cells. In conclusion, the newly established embryonic S. littoralis cells were highly susceptible to SpliMNPV, whereas the cells were non-permissive to AcMNPV, yet they still underwent programmed cell death.
CRIS-Team Scopus Importer:2019-05-24
Keywords: AcMNPV; Apoptosis; SpliMNPV; Spodoptera littoralis

Unsupervised Unstained Cell Detection by SIFT Keypoint Clustering and Self-labeling Algorithm - Mualla, Firas; Schöll, Simon; Sommerfeldt, Björn; Maier, Andreas; Steidl, Stefan; Buchholz, Rainer; Hornegger, Joachim (Lecture Notes in Computer Science, Volume 8675, MICCAI 2014 Proceedings, Part III, 2014)
We propose a novel unstained cell detection algorithm based on unsupervised learning. The algorithm utilizes the scale invariant feature transform (SIFT), a self-labeling algorithm, and two clustering steps in order to achieve high performance in terms of time and detection accuracy. Unstained cell imaging is dominated by phase contrast and bright field microscopy. Therefore, the algorithm was assessed on images acquired using these two modalities. Five cell lines having in total 37 images and 7250 cells were considered for the evaluation: CHO, L929, Sf21, HeLa, and Bovine cells. The obtained F-measures were between 85.1 and 89.5. Compared to the state-of-the-art, the algorithm achieves very close F-measure to the supervised approaches in much less time.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD5.unsupe_6

Unsupervised unstained cell detection by SIFT keypoint clustering and self-labeling algorithm. - Muallal, Firas; Schöll, Simon; Sommerfeldt, Björn; Maier, Andreas; Steidl, Stefan; Buchholz, Rainer; Hornegger, Joachim (International Conference on Medical Image Computing and Computer-Assisted Intervention (MICCAI), 2014)
We propose a novel unstained cell detection algorithm based on unsupervised learning. The algorithm utilizes the scale invariant feature transform (SIFT), a self-labeling algorithm, and two clustering steps in order to achieve high performance in terms of time and detection accuracy. Unstained cell imaging is dominated by phase contrast and bright field microscopy. Therefore, the algorithm was assessed on images acquired using these two modalities. Five cell lines having in total 37 images and 7250 cells were considered for the evaluation: CHO, L929, Sf21, HeLa, and Bovine cells. The obtained F-measures were between 85.1 and 89.5. Compared to the state-of-the-art, the algorithm achieves very close F-measure to the supervised approaches in much less time.
CRIS-Team Scopus Importer:2022-08-05

Using the Low-Pass Monogenic Signal Framework for Cell/Background Classification on Multiple Cell Lines in Bright-Field Microscope Images - Mualla, Firas; Schöll, Simon; Sommerfeldt, Björn; Maier, Andreas; Steidl, Stefan; Buchholz, Rainer; Hornegger, Joachim (International Journal of Computer Assisted Radiology and Surgery, 2014)
Purpose: Several cell detection approaches which deal with bright-field microscope images utilize defocusing to increase image contrast. The latter is related to the physical light phase through the transport of intensity equation (TIE). Recently, it was shown that it is possible to approximate the solution of the TIE using a low-pass monogenic signal framework. The purpose of this paper is to show that using the local phase of the aforementioned monogenic signal instead of the defocused image improves the cell/background classification accuracy. Materials and methods: The paper statement was tested on an image database composed of three cell lines: adherent CHO, adherent L929, and Sf21 in suspension. Local phase and local energy images were generated using the low-pass monogenic signal framework with axial derivative images as input. Machine learning was then employed to investigate the discriminative power of the local phase. Three classifier models were utilized: random forest (RF), support vector machine (SVM) with a linear kernel, and SVM with a radial basis function (RBF) kernel. Results: The improvement, averaged over cell lines, of classifying 5 x 5 sized patches extracted from the local phase image instead of the defocused image was 7.3 % using the RF, 11.6 % using the linear SVM, and 10.2 % when a RBF kernel was employed instead of the linear one. Furthermore, the feature images can be sorted by increasing discriminative power as follows: at-focus signal, local energy, defocused signal, local phase. The only exception to this order was the superiority of local energy over defocused signal for suspended cells. Conclusions: Local phase computed using the low-pass monogenic signal framework considerably outperforms the defocused image for the purpose of pixel-patch cell/background classification in bright-field microscopy. © 2013 CARS.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.usingt
Keywords: Bright-field microscopy; Cell detection; Local phase; Machine learning; Monogenic signal; Transport of intensity equation

Viscoelastic Measurements of Cells in a Rotational Rheometer - Dakhil, Haider; Wierschem, Andreas; Gilbert, Daniel; Amtmann, Anette; Hübner, Holger; Buchholz, Rainer; Friedrich, Oliver (Chemie Ingenieur Technik, 2015)
UnivIS-Import:2018-09-11:Pub.2015.tech.ITC.cbiove.viscoe

Wireless Light Emitter (WLE) zur internen Beleuchtung von Photoreaktoren - Heining, Martin; Sutor, Alexander; Lindenberger, Christoph; Buchholz, Rainer (Tagungsband, 2013)